GROUNDWATER VULNERABILITY ASSESSMENT WITH DRASTIC INDEX METHOD IN THE SOUTHWEST COASTAL REGION OF BANGLADESH: A CASE STUDY IN JESSORE DISTRICT - MUKTADIR, NAYEEM; NAOAR, LAMIA NAHIAN (My University, 2023)
The Jessore district in Bangladesh is facing a critical issue due to saline intrusion in its southwest coastal area. This research paper presents groundwater vulnerability assessment in the salinity-affected southwest coastal region of Bangladesh, focusing on the application of the DRASTIC index method in the Jessore district. Through a mix of field data and remotely sensing, the paper seeks to assess the groundwater vulnerability in the study area. The salinity level in the water in Jessore’s Keshabpur upazila was measured at 1430 micro siemens per centimeter in August 2021, although the tolerated threshold is only thought to be 670 micro siemens, according to authorities with the Bangladesh Agricultural Development Corporation (BADC). The results also point to a worrying increase in water salinity in the region, which would exacerbate an already terrible situation. As per BADC Jessore, the salinity level in the water at Keshabpur was 879 micro siemens per centimeter in 2016. Depending on the data, Abhaynagar's salinity level has ranged between 900 and 1000 micro siemens per centimeter during the past five years while Manirampur's salinity level was 1071 micro siemens per centimeter last year. The analysis reveals that 1654.91 km2 , or around 64.38 % of the Jessore district is moderately vulnerable, 31.62% is at high risk. The results of the groundwater vulnerability assessment revealed that the study area is highly vulnerable to groundwater salinization due to the presence of shallow aquifers, low recharge, and high permeability. The findings of the study provide valuable information for the groundwater management authorities to identify and prioritize the areas of high vulnerability and plan remedial measures accordingly.
Groundwater vulnerability assessment with DRASTIC index method in the southwest coastal region of Bangladesh: A case study in Jessore district